OVATE Family Protein PpOFP1 Physically Interacts With PpZFHD1 and Confers Salt Tolerance to Tomato and Yeast - Tan, Qiuping; Jiang, Shan; Wang, Ning; Liu, Xiao; Zhang, Xinhao; Wen, Binbin; Fang, Yuhui; He, Huajie; Chen, Xiude; Fu, Xiling; Li, Dongmei; Xiao, Wei; et al. (Frontiers in Plant Science, 2021)
The OVATE Family Protein (OFP) genes (OFPs) have been shown to respond to salt stress in plants. However, the regulatory mechanism for salt tolerance of the peach (Prunus persica) OFP gene PpOFP1 has not been elucidated. In this study, using yeast two-hybrid screening, we isolated a nucleus-localized ZF-HD_dimer domain protein PpZFHD1, which interacts with the PpOFP1 protein in the peach cultivar ‘Zhongnongpan No.10’. A segmentation experiment further suggested that the interaction happens more specifically between the N-terminal, contains ZF-HD_dimer domain, of PpZFHD1 and the C-terminal, consists of OVATE domain, of PpOFP1. Additionally, quantitative real-time polymerase chain reaction (qRT-PCR) experiments indicate that transcription of these two genes are induced by 200 mmol/L (mM) NaCl treatment. Heterogeneous transformation experiments suggested that the growth status of transformed yeast strain over-expressing each of these two genes was more robust than that of control (CK). Furthermore, transgenic tomato plants over-expressing PpOFP1 were also more robust. They had a higher content of chlorophyll, soluble proteins, soluble sugars, and proline. Activities of the superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) in these plants were higher, and tissues from these plants exhibited a lower relative conductivity and malondialdehyde (MDA) content. These results suggest that PpOFP1 physically interacts with PpZFHD1 and confers salt tolerance to tomato and yeast, thus revealing a novel mechanism for regulating salt tolerance in peach and other perennial deciduous trees.